MANAJEMEN WAKAF PRODUKTIF: Studi Analisis Pada Baitul Mal Di Kabupaten Kudus - Sa'adah, Nailis; Wahyudi, Fariq (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
The purpose of this study was to analyze the funding management, development management, utilization management and reporting management of productive ‘waqf’/endowment in Baitul Mal Kudus. This study was a qualitative research and data were collected through interviews, observation and documentation. The results showed that based on productive endowment is part of management system. It can be seen if human resources are skillful and professional in managing endowments, the productivity of endowments funding and development will be increased and can include broader utilization in both usage and distribution of endowment property. Baitul Mal which develops the endowments will have major contributions to the society in education, economy, health or other social helps.